(untitled) (Fiep Bulletin - online, 2013)
In this present work it was investigated about the Profile of Physical Education Professional who work at academies of physical activity in the Parintins Town / Am. The sample was composed of 15 professionals working in several modalities in five gyms. As methodological foundation, it was opted for the approach of a descriptive search, using as an instrument for data collection and information a questionnaire containing 15 directed questions. It was found that there are a greater number of male professionals that most of those professionals working in these academies haven’t got a record at the Regional Council of Physical Education (RCPE) and many of them haven’t got an adequate professional formation to exercise the function, haven’t got qualified technical conditions to attend the clientele in this area. It was also checked that most professionals working in gyms are planning their lessons and that they use the physical assessment as the main method for prescribing of exercises and those are acting a little more than a year in the profession. According to this data, it is necessary competence and professional skills that will only be complete if it is grounded in a body of scientific and technical knowledge that supports the practice of Professional Physical Education who works both in working out and bodybuilding gyms such as in other areas.